Batak and Java Ethnic Culture Communication Strategy in Galang Suka Village, Kecamatan Galang, Kabupaten Deli Serdang - Devi Khairunnisa Hasibuan; Muhammad Alfikri (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
Communication between cultures is communication between people from different cultures. This process is also rarely as smooth and error-free. The cultural differences that make it difficult for us to interact and communicate. The purpose of this research is to: (1) understand how the culture process of communication between Bataknese and Javanese at Galang Suka Village, Districts Galang, Regency of Deli Serdang, (2) Determine the source of the communication barrier in Bataknese and Javanese culture at Galang Suka Village, Districts Galang, Regency of Deli Serdang. This study employs the qualitative method with a descriptive approach and data collection techniques such as interviewing, observation, and documentation. The findings of this study explain why the communication blocker is not working effectively. The communication barrier occurs due to the stereotyping of feelings, languishment, and alienation. Even though there is a communication barrier, they continue to interact with different ethnic groups.